Managing Othering from a Leadership Perspective - Steinmetz, Carl H. D.; Salim, Dliman (Advances in Social Sciences Research Journal, 2023)
Goals: How to counter othering is the main topic of this article. There is an important role for government leaders, politicians, CEOs, chief executives and service leaders in addressing othering. Othering is more widespread than we think. The academic literature focuses mainly on belonging. Perhaps because this focus serves the neoliberal agenda of competition and success. This article also discusses the various theories related to othering. Professor Dr. Lewis R. Gordon’s philosophical work on othering is crucial. Method: A literature review and empirical research, mainly large and small surveys, were used. Results. Othering is a many-headed monster. Othering facilitates (neo-) colonization and (modern) slavery, wars and genocide, institutional and structural racism, the manipulation of a society to make it a class society with a significant class of haves and have-nots, and everyday racism between (groups of) individuals. The approach is multifaceted. To counter othering, lawsuits against corporations and institutions can be used to enforce reparations (aimed at restoring the perpetrator’s morale) and further by activating witness interventions. Because social media facilitate othering, it is useful to distinguish between the real and virtual worlds. This is also because the effects of these worlds merge. Othering through social media is very threatening. In this article, a "Human Appreciation Ratio" was developed. The concrete concept questionnaire is included in Appendix 1. This ratio is a measure of the sense of belonging and othering experiences. With this ratio, companies, institutions, and governments can determine how well they deserve the labels they have given themselves, such as "diverse and inclusive”. The theoretical underpinnings of othering arose long ago when Westerners viewed non-Westerners as inferior. This began during the Enlightenment with the distinction between the so-called traditional world (non-Western world) and the modern world (Western world, especially Europe).